2014
DOI: 10.1089/acm.2014.0077
|View full text |Cite
|
Sign up to set email alerts
|

So-Eum Type as an Independent Risk Factor for Irritable Bowel Syndrome: A Population-Based Study in Korea

Abstract: Objectives: It has been hypothesized that Sasang constitutional types (SCTs) have a specific hypoactive organ, which can account for vulnerability to related diseases or symptoms. This study examined the relationship between SCTs and irritable bowel syndrome (IBS). Design: Cross-sectional study in a population-based cohort study in Korea. Participants: 1362 individuals (705 men and 657 women) who participated in the Korean Genome and Epidemiology Study. Outcome measures: The participants were classified into S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
(47 reference statements)
0
8
1
Order By: Relevance
“…No significant difference was observed in the complexion according to the Cold- and Heat-prescription groups for the overall male and female groups consisting of the Tae-Eum, So-Eum, and So-Yang types, but significant differences were found for each Sasang constitution. To date, differences according to Sasang constitution have been the primary focus of studies [ 16 , 17 ], but our results show differences within the same Sasang constitution. In addition, the results were consistent with the TKM literature.…”
Section: Discussioncontrasting
confidence: 50%
“…No significant difference was observed in the complexion according to the Cold- and Heat-prescription groups for the overall male and female groups consisting of the Tae-Eum, So-Eum, and So-Yang types, but significant differences were found for each Sasang constitution. To date, differences according to Sasang constitution have been the primary focus of studies [ 16 , 17 ], but our results show differences within the same Sasang constitution. In addition, the results were consistent with the TKM literature.…”
Section: Discussioncontrasting
confidence: 50%
“…These stress hormones have a harmful effect on multiple target organs and systems, with outcomes including chronic pain, immunosuppression, and psychological disorders [ 24 , 25 ]. Our results suggest a partial explanation of clinical data showing that Soumins are vulnerable to stress and irritable bowel syndrome (IBS) [ 8 ]. Individuals with IBS were known to have the sustained HPA axis activity [ 26 ], and then Soumins showed the highest levels of both cortisol and adrenaline in our study.…”
Section: Discussionmentioning
confidence: 64%
“…Current genetic science has shown that the genome critically affects the complex processes involved in health and disease [ 5 ], and the SCM classification is presumably related to macrolevel genomic differences among individuals [ 6 ]. Moreover, recent studies have found that certain Sasang types are significantly more susceptible to certain diseases; specifically, those with the Taeumin type are especially susceptible to metabolic syndrome, and those with the Soumin type are especially susceptible to irritable bowel syndrome (IBS) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies have reported that subjects of certain Sasang classifications are notably more susceptible to some disorders; e.g., Taeumin for type 2 diabetes and metabolic syndrome [ 33 , 34 ] and Soumin for irritable bowel syndrome [ 35 ]. We are unable to explain the mechanisms responsible for the association between Sasang constitution and the tendency to develop particular disorders, including FD.…”
Section: Discussionmentioning
confidence: 99%